1985
DOI: 10.1007/bf02560279
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal Crohn's disease

Abstract: A group of 86 patients with anorectal Crohn's disease were followed up from ten to 40 years to determine the course of the disease and the number of patients who later required proctectomy. The overall cumulative probability of avoiding proctectomy was 91.6 percent at ten years and 82.5 percent at 20 years. Resection of all proximal Crohn's disease did not ameliorate the anorectal disease, except in patients who had all proximal disease removed and had no recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…It has been also reported that 20% of patients receiving colectomy will require proctectomy within 5 years [19]. These observations justify the disturbingly high rate of proctectomy still observed, ranging between 10 and 18% [10, 49]. Recently, IFX proved to be effective in CD patients with failed ileorectal anastomosis candidates to proctectomy, preserving the rectum in 10/12 patients (83.3%) [78].…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been also reported that 20% of patients receiving colectomy will require proctectomy within 5 years [19]. These observations justify the disturbingly high rate of proctectomy still observed, ranging between 10 and 18% [10, 49]. Recently, IFX proved to be effective in CD patients with failed ileorectal anastomosis candidates to proctectomy, preserving the rectum in 10/12 patients (83.3%) [78].…”
Section: Treatmentmentioning
confidence: 99%
“…Genetic and epigenetic factors play a pivotal role in CD, as the risk of developing CD and its related complications is higher in relatives of CD patients than in general population [5, 8]. Genetic susceptibility is suggested by the frequent association between perianal CD and colorectal as well as upper gastrointestinal disease involvement [9, 10] so that CD is a different entity from penetrating abdominal CD [9] and is also associated with worse prognosis in the long term [11]. Also, as active, persisting disease leads to fibrosis in CD [5], a hypoxia-mediated mechanism could also play a role [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these, most patients have undesirable results, which can lead to proctectomy in 10%–18% of cases. [1112131415]…”
Section: Introductionmentioning
confidence: 99%
“…Seventy-two percent of patients with colorectal CD will undergo a surgical treatment [3]; proctectomy with permanent stoma will be the choice in about 20% of patients with perianal disease [4,5]. …”
Section: Introductionmentioning
confidence: 99%